Pengaruh Islam dan Eropa dalam Budaya Kuliner di Keraton Yogyakarta dan Surakarta Abad 19 dan 20 Masehi - Ajid Thohir; Bambang Muhamad Fasya Azhara (Universitas Gadjah Mada, 2022)
Islam and Europe are an integral part of the life of Keraton Yogyakarta and Surakarta, especially in the culinary culture of the keraton. This study aims to identify of the influence of Islam and Europe on culinary cultures at keraton yogyakarta and surkarta in the 19-20 centuries c.e., as well as the forms resulting from that influence. T he research methods used historical research methods, which refer to various sources categorized into primary and secondary sources. The p rimary sources include photo archives, newspapers, to invitation cards. As for secondary sources it is made up of books and articles. The results of this research identify what is h alal or lawful and haram or prohibited in the culinary culture. The keraton thus attempted to modify a variety of European dishes to be enjoyed without violating islamic teachings. As for the European influence, the rijsttafel, the orchestra, the ingredients used, to the use of a foreign language on the dinner table. Such European influence arose because of the process of interaction between Javanese nobles and europeans, the keraton attempted to imitate European customs.